CHAPTER 8: Fluoride Levels in Herbal and Tea Infusions - (:unkn) unknown (Royal Society of Chemistry, 2015)
Tea is among the most consumed beverages all over the world. Therefore investigating the effects of tea drinking on health is an unavoidable issue. Tea plant tree contains fluoride and many factors affect the fluoride content in tea. Daily tea drinking contributes to the daily fluoride intake significantly. Fluoride toxicity is an important health problem that may occur due to many factors including tea drinking. Herbal infusions are also becoming popular beverages and fluoride content of herbal infusions has also been investigated. This chapter reviews the fluoride content in tea and herbal infusions and their potential health effects. © The Royal Society of Chemistry 2015.